1986
DOI: 10.1007/bf01412607
|View full text |Cite
|
Sign up to set email alerts
|

Low-angle X-ray investigations of detergent treated soft keratins

Abstract: Keratins forming the main bulk of the horny layer of the epidermis and epidermis appendages such as hair, nails, claws, scales and feathers can be divided into two classes, namely hard and soft keratins. All mammalian keratins (hard and soft keratins) yield a typical a-pattern with a 5.15 A. meridional reflexion and a 9.8 ]k equatorial reflexion. These keratins are called a-keratins. Apart from this, some mammalian hard keratins such as mohair fibres and porcupine quills yield very sharp low-angle X-ray patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The water in the space between the microfibrils and the globular matrix is believed to be directly concerned with wool swelling [3,43]. Swift et al reported that the relatively uncrosslinked proteins of the intermacrofibrillar matrix are binding water and can be regarded as the main plasticizing elements separating the stiffer macrofibrils [44,45].…”
Section: Location Of Interstitial Water 'mentioning
confidence: 99%
“…The water in the space between the microfibrils and the globular matrix is believed to be directly concerned with wool swelling [3,43]. Swift et al reported that the relatively uncrosslinked proteins of the intermacrofibrillar matrix are binding water and can be regarded as the main plasticizing elements separating the stiffer macrofibrils [44,45].…”
Section: Location Of Interstitial Water 'mentioning
confidence: 99%